"The culture of fear" of inhabitants of EU countries in their reaction to the COVID-19 pandemic – A study based on the reports of the Eurobarometer. (March 2021) - Gruchoła, Małgorzata; Sławek-Czochra, Małgorzata
Abstract: The aim of the paper was a study of public opinion of the inhabitants of the European Union as regards the reaction and perception of the COVID-19 pandemic on the basis of weekly reports of the Eurobarometer: Public opinion monitoring in the time of COVID-19, containing data from member EU countries (March-July 2020: first wave of pandemic). It was assumed that during the first wave of the Covid-19 pandemic, the lack of a sense of security (health, economic and social) was the result not by personal experience (a real threat), but was cultivated and communicated by the media, creating a culture of fear. The opinions were analyzed in three problem domains: health, economy and society, taking into account fears and their functions, experiences and declarations for solving the problems generated by the pandemic. A quantitative analysis of the content of the reports was applied as well as a qualitative analysis of the content and an analytical-descriptive one. Seven research hypotheses were accepted, of which 3 were affirmed: fear of the COVID-19 pandemic and its effects is presently a more widespread problem than the pandemic itself. The level of fear as regards the effects of the pandemic exceeds the level of negative experiences. In the domain of the health effects, the greatest fear is engendered by contact with COVID-19 which may cause infection: 14 fears. The remaining hypotheses were refuted: the level of fear of inhabitants of EU countries regarding health consequences/dangers (46) does not exceed the level of fear regarding economical (75) and social (19) consequences/dangers. In the domain of economical consequences/dangers, the most fears: 37, are caused by fear of an economical crisis and not one of unemployment (17) - as was assumed. Social isolation is more often experienced (13) and present in declarations (16) of inhabitants of the EU than in their fears (4). Fears of the consequences/dangers of COVID-19 plays, most of all, a negative function (137/74) and not a positive one - as assumed.